Strategi Pembelajaran Keterampilan Speaking - Devi Indah Wulansari; Aip Syaepul Uyun (Jurnal Dimamu, 2023)
English in speaking skills. Referring to English as the world's largest lingua franca or social language, English today has become the second most spoken language after Chinese. Furthermore, its status has been made as one of the languages that must be learned in almost all countries in the world. Therefore the need to always improve the quality of teaching is fundamental. But in practice, teaching and learning English in the classroom still leaves a lot of homework, especially those related to speaking teaching strategies. The low quality of graduate students in Indonesia in the field of speaking has proven that there is a pattern that needs to be addressed from the English language teaching system in our country. Therefore this study aims to provide an understanding of several types of language teaching strategies that can be implemented in the classroom. By using the method of library research or literature. This article provides an understanding and description of the types of learning strategies that can be used when teaching English.